2004
DOI: 10.1074/jbc.m403527200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress/Damage Induces Multimerization and Interaction of Fanconi Anemia Proteins

Abstract: Fanconi anemia (FANC) is a heterogeneous genetic disorder characterized by a hypersensitivity to DNAdamaging agents, chromosomal instability, and defective DNA repair. Eight FANC genes have been identified so far, and five of them (FANCA, -C, -E, -F, and -G) assemble in a multinuclear complex and function at least in part in a complex to activate FANCD2 by monoubiquitination. Here Fanconi anemia (FANC) 1 is an autosomal recessive disorder characterized by chromosomal instability and defective DNA repair, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…The FA proteins are thus believed to play important roles in the maintenance of hematopoiesis. Consistent with the observations that cells derived from FA patients are intolerant of oxidative stress, it has been reported that FA proteins, particularly the complementation group C (FANCC) protein, play a crucial role in oxidative-stress signaling in a variety of cell types including hematopoietic cells (Kruyt et al, 1998;Cumming et al, 2001;Hadjur et al, 2001;Futaki et al, 2002;Park et al, 2004;Saadatzadeh et al, 2004;Pagano et al, 2005). More recently, cytokine hypersensitivity of FA hematopoietic cells to apoptotic cues has also been proposed as a major factor in the pathogenesis of BM failure in three FA mouse models…”
Section: Introductionmentioning
confidence: 65%
“…The FA proteins are thus believed to play important roles in the maintenance of hematopoiesis. Consistent with the observations that cells derived from FA patients are intolerant of oxidative stress, it has been reported that FA proteins, particularly the complementation group C (FANCC) protein, play a crucial role in oxidative-stress signaling in a variety of cell types including hematopoietic cells (Kruyt et al, 1998;Cumming et al, 2001;Hadjur et al, 2001;Futaki et al, 2002;Park et al, 2004;Saadatzadeh et al, 2004;Pagano et al, 2005). More recently, cytokine hypersensitivity of FA hematopoietic cells to apoptotic cues has also been proposed as a major factor in the pathogenesis of BM failure in three FA mouse models…”
Section: Introductionmentioning
confidence: 65%
“…FA cells are sensitive to ROS, thus acquiring abnormalities in several redox status end points (13)(14)(15). FANCA and FANCG are redox-sensitive proteins that are multimerized to form a nuclear complex in response to oxidative stress (16). Not surprisingly, the survival of human primary FA BM cells can be ameliorated by reducing oxidative stress (14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, FANCA and FANCG are sensitive to redox conditioning, such that hydrogen peroxide treatment triggers complex formation of these FA proteins. 120 The antioxidant tempol displayed tumor onset and protective effects against oxidative damage in Fancd2 2/2 mice.…”
Section: Fa Pathway and Cytokinesismentioning
confidence: 99%